Crafting History in the Northern Plains : A Political Economy of the Heart River Region, 1400-1750 - Mitchell, Mark D. (Book collections on Project MUSE., 2013)
In this book, the author illustrates the crucial role archaeological methods and archaeological data can play in producing trans-Columbian histories. Combining an in-depth analysis of the organization of stone tool and pottery production with ethnographic and historical data, the author synthesizes the social and economic histories of the native communities located at the confluence of the Heart and Missouri rivers, home for more than five centuries to the Mandan people.